Epoxy/anhydride networks modified by epoxy/anhydride oligomers containing SiOH groups - Mauri, Adriana Noemi (2000)
Epoxy/anhydride oligomers containing variable amounts of trialkoxysilane groups were synthesized from phenyl glycidyl ether (PGE), 3-glycidoxypropyl trimethoxysilane (GPMS), and methyl tetrahydrophthalic anhydride (MTHPA), using benzyldimethylamine (BDMA) as an initiator. They were hydrolyzed and partially condensed using diluted formic as a catalyst, with the last step carried out in a solution of diglycidyl ether of bisphenol A (DGEBA). By curing with a stoichiometric amount of MTHPA, in the presence of BDMA, plasticized epoxy/anhydride networks were obtained without any evidence of phase separation. These materials showed a better abrasion resistance than that of the neat matrix. The presence of free SiOH groups can be used to improve the adhesion to glass surfaces.